Pengaruh Kepercayaan Diri dan Berani Mengambil Resiko Terhadap Niat Berwirausaha pada Masyarakat Kelurahan SEKIP Kecamatan Medan Petisah - Fahruddin Sani; Herry Syahrial; Isnaniah Isnaniah (Universitas Medan Area, 2022)
This study aims to examine the effect of self-confidence and the courage to take risks on entrepreneurial intentions in the SEKIP Village Community, Medan Petisah District. This type of research is quantitative associative. The method of data collection in this study was done by distributing questionnaires. The sampling technique used in this study used convenience sampling/accidental sampling with a sample of 100 people. Based on the results of the study, it was found that there was a positive influence of self-confidence and the courage to take risks on entrepreneurial intentions in the SEKIP Village Community, Medan Petisah District.